Two-dimensional Numerical Simulations of Mixing under Ice Keels Python Code - De Abreu, Sam; Cormier, Rosalie M.; Schee, Mikhail G.; Zemskova, Varvara E.; Rosenblum, Erica; Grisouard, Nicolas (Zenodo, 2023)
This deposition contains the Python code used in running two-dimensional mixing simulations of two-layered flow under the cross-section of an ice keel and processing the resultant output. A description of the uploaded files: Constants.py : Contains all parameter values like keel depth and width, stratification values, domain dimensions, specification of the spatial grid and time-stepping scheme, flow speed, etc. This file is used in nl_strat_simulation.py and compute_diffusivitymixdepth.py . nl_strat_simulation.py : The simulation code. Note that it utilizes Dedalus 2 ( https://dedalus-project.org/ ), a spectral PDE solver, hence a proper installation of the module is required to run the code. compute_diffusivitymixdepth.py : Reads in the output from the simulation and computes mixing rates (phi_d), diapycnal diffusivity values (K), and depth of mixing for each time slice (z_mix). All of these values are then stored in JSON files for further analysis. arctic_regime_figure.py : Used to create a figure that depicts specific Arctic regions' locations in a Froude-number-dimensionless-keel-draft space (on average) as well as predictions as to where the averages will be in 5 to 15 years (Figure 9). This file includes all calculations and plotting code. Note that the Python version required to run the code is constrained by the version required to run Dedalus 2. Python 3 should be sufficient.